2021
DOI: 10.3390/f12040395
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Machine Learning Algorithms for Modeling the Spatial Distribution of Bark Beetle Infestation

Abstract: Machine learning algorithms (MLAs) are used to solve complex non-linear and high-dimensional problems. The objective of this study was to identify the MLA that generates an accurate spatial distribution model of bark beetle (Ips typographus L.) infestation spots. We first evaluated the performance of 2 linear (logistic regression, linear discriminant analysis), 4 non-linear (quadratic discriminant analysis, k-nearest neighbors classifier, Gaussian naive Bayes, support vector classification), and 4 decision tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the future, we also hope to expand the curriculum of GIS714 at North Carolina State University to include additional geocomputation domains such as machine‐learning algorithms (MLAs), clustering and classification and the processing and analysis of remote sensing data. For example, the r.learn and v.class tool families both include several machine learning classification algorithms and they have been applied in several studies (Flasse et al, 2021; Koreň et al, 2021; Silver et al, 2019). GRASS GIS can also be integrated with third‐party MLAs like MaxEnt (Andreo et al, 2021) which could be demonstrated using a notebook tutorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we also hope to expand the curriculum of GIS714 at North Carolina State University to include additional geocomputation domains such as machine‐learning algorithms (MLAs), clustering and classification and the processing and analysis of remote sensing data. For example, the r.learn and v.class tool families both include several machine learning classification algorithms and they have been applied in several studies (Flasse et al, 2021; Koreň et al, 2021; Silver et al, 2019). GRASS GIS can also be integrated with third‐party MLAs like MaxEnt (Andreo et al, 2021) which could be demonstrated using a notebook tutorial.…”
Section: Discussionmentioning
confidence: 99%
“…GRASS GIS is an open‐source Geographic Information System (GIS) software that provides powerful raster, vector, and geospatial processing tools, accessible through a GUI, Python API, command‐line API, and integration with QGIS and R (Landa et al, 2022; Neteler & Mitasova, 2013). Tools, which are referred to as modules in the GRASS GIS documentation, include advanced terrain and hydrological modeling (Harmon et al, 2019; Jasiewicz & Stepinski, 2013; Mitasova et al, 2004), satellite and aerial imagery processing (Rocchini, Petras, Petrasova, Chemin, et al, 2017; Rocchini, Petras, Petrasova, Horning, et al, 2017), point cloud processing (Petras et al, 2017), visualization of raster and vector data and, clustering and classification algorithms including machine‐learning methods (Flasse et al, 2021; Koreň et al, 2021; Silver et al, 2019). For multi‐temporal raster and vector data, GRASS GIS provides a temporal framework with associated processing and visualization tools (Gebbert & Pebesma, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ML uses algorithms that analyse data, learn from it, and then employ the knowledge gained to propose intelligent solutions. The need for analysing massive amounts of RS data then led to the development of deep learning (DL), based on a hierarchy of concepts [25]. In contrast to ML, DL algorithms, like convolutional neural networks (CNNs), use the raw input RS data as a training set to perform advanced (deep) self-learning, and require high-performance computer power [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Associating the knowledge generated from the application of data wrangling in a dataset with machine learning algorithms can promote intelligent decision making. The union of techniques of machine learning can improve the system performance of cut-tolength timber, forest resources, and services management [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%